Catalytic Asymmetric Vinylogous and Bisvinylogous Propargylic Substitution - Qian, Hao-Dong; Li, Zhi-Heng; Deng, Shuang; Yao, Chaochao; Xiang, Hua-Ming; Xu, Guang; Geng, Zi-Qi; Wang, Zihao; Chen, Linfeng; Liu, Chunrong; Zhu, Cuiju; Qi, Xiaotian; et al. (Journal of the American Chemical Society, 2022)
Distinct regio- and enantioselectivity control in copper-catalyzed vinylogous and bisvinylogous propargylic substitution has been accomplished by using a novel chiral N,N,P ligand. The developed method provides an efficient and selective approach to an array of highly enantioenriched alkynyl unsaturated carbonyl compounds. Salient features include excellent functional group tolerance and broad substrate scope. The synthetic utility of the developed method is further demonstrated by a gram-scale synthesis and by application to a range of transformations including enantioselective synthesis of unique challenging compounds.